Expression and roles of Slit/Robo in human ovarian cancer - Dai, Cai Feng (2011)
The Slit glycoproteins and their Roundabout (Robo) receptors regulate migration and growth of many types of cells including human cancer cells. However, little is known about the expression and roles of Slit/Robo in human ovarian cancer. Herein, we examined the expression of Slit/Robo in human normal and malignant ovarian tissues and its potential participation in regulating migration and proliferation of human ovarian cancer cells using two ovarian cancer cell lines, OVCAR-3 and SKOV-3. We demonstrated that Slit2/3 and Robo1 were immunolocalized primarily in stromal cells in human normal ovaries and in cancer cells in many histotypes of ovarian cancer tissues. Protein expression of Slit2/3 and Robo1/4 was also identified in OVCAR-3 and SKOV-3 cells. However, recombinant human Slit2 did not significantly affect SKOV-3 cell migration, and OVCAR-3 and SKOV-3 cell proliferation. Slit2 also did not induce ERK1/2 and AKT1 phosphorylation in OVCAR-3 and SKOV-3 cells. The current findings indicate that three major members (Slit2/3 and Robo1) of Slit/Robo family are widely expressed in the human normal and malignant ovarian tissues and in OVCAR-3 and SKOV-3 cells. However, Slit/Robo signaling may not play an important role in regulating human ovarian cancer cell proliferation and migration.